Highly luminescent gold nanocluster assemblies for bioimaging in living organisms. Issue 6 (20th December 2021) - Yu, Fanfan; Cao, Zheng; He, Shiyu; Xiang, Hui; Zhao, Gan; Yang, Lina; Liu, Honglin
Abstract : Fabrication of highly luminescent and functionalized gold cluster nano-assembled structures for low-background and high-sensitivity sensing and imaging of the GSH molecule in cells and living organisms. Abstract : Fluorescent gold nanoclusters are promising nanomaterials for biomedical applications but confronted with low emission efficiency and poor surface functionality. Herein, three kinds of highly luminescent and functionalized gold nanocluster nano-assembled structures were fabricated by poly-l -arginine surface engineering for luminescence improvement. The assembly is employed for imaging the glutathione molecule in cells and living organisms with low background and high sensitivity.